Celebrity Endorsement Influence on Destination Image - Marković, Ivana; Radosavljević, Gordana; Borisavljević, Katarina (Naše gospodarstvo/Our economy, 2022)
Destination image influences the tourist decision-making process, and their intention to visit, revisit and recommend. Therefore, a positive destination image is considered one of the key destination success factors. Tourists will form the image according to their own or others’ experiences and information related to the destination, one option to provide destination information is one of the most effective promotional tools called celebrity endorsement. With the assumption that a positive celebrity image will be transferred to the destination, this study will explore the effect of celebrity endorsement on destination image. The study aims to test the celebrity endorsement effect on destination image through the source attractiveness model, source credibility model, and the Match-up model. Data were collected using the online survey technique, the sample size was 204 respondents. Research hypotheses were tested by regression analysis. Results indicated that celebrity attractiveness, trustworthiness, expertise, and match-up impact the destination image. The theoretical contribution is reflected in new information regarding the role of celebrity endorsement in tourism, which is limited in foreign and domestic scientific literature. As a practical contribution, the study provides information that may be useful to tourism service providers in creating a promotional campaign.